2023
DOI: 10.1093/rheumatology/kead057
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy decreases in rheumatic diseases, long-term concerns remain in myositis: a comparative analysis of the COVAD surveys

Abstract: Objective COVID-19 vaccines have a favorable safety profile in patients with autoimmune rheumatic diseases (AIRDs) such as idiopathic inflammatory myopathies (IIMs), however hesitancy continues to persist among these patients. Therefore, we studied the prevalence, predictors, and reasons for hesitancy in patients with IIMs, other AIRDs, non-rheumatic autoimmune diseases (nrAIDs) and healthy controls (HCs), using data from the two international COVID-19 Vaccination in Autoimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…These doubts may then become less pressing when risk perception is higher, leading to a change in attitude toward the need for a vaccine. Acceptance regardless of fear is consistent with other studies, which have reported a decrease in hesitancy from 2021 to 2022 despite increase in concerns over long-term safety of vaccines [29].…”
Section: Discussionsupporting
confidence: 90%
“…These doubts may then become less pressing when risk perception is higher, leading to a change in attitude toward the need for a vaccine. Acceptance regardless of fear is consistent with other studies, which have reported a decrease in hesitancy from 2021 to 2022 despite increase in concerns over long-term safety of vaccines [29].…”
Section: Discussionsupporting
confidence: 90%
“…Rheumatology and dermatology are similar in that many conditions have an autoimmune basis in its pathogenesis. Similar concerns about vaccine safety and the potential exacerbation of underlying inflammatory conditions have been observed among patients with myositis, rheumatic diseases, including systemic lupus erythematosus, and rheumatoid arthritis [ 18 , 19 , 20 ].…”
Section: Dermatology Patients and Attitude Towards Covid-19 Vaccinationmentioning
confidence: 81%
“…The phenomenon of denial is significant, and reports of adverse effects, particularly thrombotic ones, have a bearing on it. A complicated phenomenon, vaccination hesitancy is influenced by people's opinions of the effectiveness and safety of immunizations; therefore, more studies should focus on the safety and more studies should investigate vaccine fear in people [178][179][180].…”
Section: Global Benefit/risk Ratio Of the Various Vaccination Types F...mentioning
confidence: 99%